Modelling and evaluation of nutrients (N, P, K) flow for chicken manure - Rozali, Nurulfarhani (2015)
The concept of modeling system widely focused on assessing and evaluating nutrients flow (nitrogen, phosphorus and potassium) from feed to manure and manure to compost. The aim of this study is to develop chicken manure utilization modeling system at farm with the estimation of the nutrients in the manure. The model was developed by calibrating the data from previous experiment done by Diyana (2014). The modeling systems involve two models; (1) Production and housing stage and (2) Manure handling stage. Both models were process-based models that based on input equal to output concept. In the production and housing stage, the user interface described about the operation of nutrients flow. The interface allows the input; any changes in the data will change the value shown in the model. By using the interface, all nutrients input are estimated from the nutrient in feed, nutrients in chicken manure and the nutrients that retained in the manure. It can be evaluated according to the number of animals in the farm. The modeling can show the total amount of nutrients in the manure that might be loss to the environment and might polluted the environment which will leave an adverse impact to the society. The nitrogen content loss by ammonia volatilization to the atmosphere while phosphorus and potassium loss by runoff and leaching from the rain and contaminate the ground surface. The composting flow in the manure handling stage estimates the total nutrients available from the fresh manure. The nutrients losses during composting make the nutrients readily available to be applied to the soil directly as nutrient resources. Then, the model validation was made after the model calibration. The purpose of manure collection and composting done is validating the model. The result from both steps (Step 1: Manure collection, Step 2: Composting) were used to validate the current data with the previous data by Diyana (2014) which has been calibrated. In the first step, the manure was collected at Unit Poultry Ladang 2, UPM weekly on Friday morning. All the 100 birds were assigned into one battery cages with individual crates. One bird per one crate to make ease in collecting the feces. While in the second step, six piles of compost were assigned randomly for two treatments (with EM and without EM) with three replicates for each treatment (R1, R2, R3). Based on the results from step 1 and step 2, the validation of the data was presented in the graph. The regression line in the graphs showed the accuracy of the value in the graph and the 1:1 line is the balanced of prediction and observation works. Overall, the model validation in the production and housing stage and manure handling stage showed that the nutrients were underestimates. The study on nutrient loss in production and housing stage, and manure handling stage should be carried out for further model improvement.